Fluorescently-tagged magnetic protein nanoparticles for high-resolution optical and ultra-high field magnetic resonance dual-modal cerebral angiography. Issue 47 (28th November 2022) - Mishra, Sandeep K.; Herman, Peter; Crair, Michael; Constable, R. Todd; Walsh, John J.; Akif, Adil; Verhagen, Justus V.; Hyder, Fahmeed
Abstract : In vivo cerebrovascular imaging with fluorescently-tagged magnetic protein nanoparticles (f-MPNPs) enhances microvascular contrast for simultaneous visualization by whole-brain time-of-flight MRI angiography and high resolution fluorescence imaging. Abstract : Extremely small paramagnetic iron oxide nanoparticles (FeMNPs) (<5 nm) can enhance positive magnetic resonance imaging (MRI) contrast by shortening the longitudinal relaxation time of water ( T 1 ), but these nanoparticles experience rapid renal clearance. Here, magnetic protein nanoparticles (MPNPs) are synthesized from protein-conjugated citric acid coated FeMNPs (c-FeMNPs) without loss of the T 1 MRI properties and tagged with fluorescent dye (f-MPNPs) for optical cerebrovascular imaging. The c-FeMNPs shows average size 3.8 ± 0.7 nm with T 1 relaxivity ( r 1 ) of 1.86 mM −1 s −1 and transverse/longitudinal relaxivity ratio ( r 2 / r 1 ) of 2.53 at 11.7 T. The f-MPNPs show a higher r 1 value of 2.18 mM −1 s −1 and r 2 / r 1 ratio of 2.88 at 11.7 T, which generates excellent positive MRI contrast. In vivo cerebral angiography with f-MPNPs enables detailed microvascular contrast enhancement for differentiation of major blood vessels of murine brain, which corresponds well with whole brain three-dimensional time-of-flight MRI angiograms (17 min imaging time with 60 ms repetition time and 40 μm isotropic voxels). The real-time fluorescence angiography enables unambiguous detection of brain capillaries with diameter < 40 μm. Biodistribution examination revealed that f-MPNPs were safely cleared by the organs like the liver, spleen, and kidneys within a day after injection. Blood biochemical assays demonstrated no risk of iron overload in both rats and mice. With hybrid neuroimaging technologies ( e.g., MRI-optical) on the rise, f-MPNPs built on this platform can generate exciting neuroscience applications.